Causes of Reduced Seawater Pump Pressure on Board KM Amukti Palapa - Andi Setiawati; P. Parawansa; Andi Murtafiah; Yuyu Ruhayu; Andi Herlina (Golden Ratio of Mapping Idea and Literature Format, 2026)
This study aims to identify the factors causing reduced seawater pump pressure on board KM Amukti Palapa, examine the impacts of pressure reduction on pump performance, and propose appropriate maintenance measures to ensure normal operation. The research employed a descriptive qualitative approach using data collected through direct observation, interviews with engine officers and technical personnel, documentation review, and relevant literature studies. The findings indicate that reduced seawater pump pressure is primarily caused by discharge valve leakage, blockages in the discharge line, pump overloading, impeller damage, and human error. These conditions may result in unstable pump loading, cavitation, inefficient energy consumption, damage to seals, bearings, piping systems, and increased maintenance costs. The study further highlights the importance of implementing a comprehensive preventive maintenance program, including routine inspections, component replacement, cleaning procedures, performance monitoring, crew training, and proper documentation. Effective maintenance management and continuous monitoring can significantly improve pump reliability, reduce operational disruptions, and extend the service life of seawater pump systems on board vessels.